Contamination characteristics, spatial distribution and ecological-health risk assessment of legacy and current-use pesticides: a case study in the Beibu Gulf - Zhang, Li; Ma, Jiaxin; Liu, Peipei; Qi, Anxiang; Jin, Haiyan; Jia, Renming; Zheng, Zhenming; Yan, Cheng; Cai, Minghong (Frontiers in Marine Science, 2023)
With the prohibition of conventional organochlorine pesticides (OCPs), the extensive use and continuous release of current-use pesticides (CUPs), such as organic amine pesticides (OAPs) and organophosphate pesticides (OPPs), in agriculture and mariculture activities have raised global attention. In this study, the occurrence and distribution of 36 pesticides from above 3 categories were investigated in seawater and sediment in Beibu Gulf, a typical subtropical agricultural and maricultrual zone. Results showed that pesticides were widely present in this region with the total concentration ranging from 0.36 to 21.07 ng/L in seawater and from 0.02 to 9.73 ng/g dw in sediment. OAPs and OPPs were the most abundant categories contributing 74% and 66% to the total pesticides burden in seawater and sediment, respectively, revealing the current-use pesticides as substitutes of legacy organochlorine pesticides (OCPs) were mainly used in surrounding areas. For both seawater and surface sediment, the spatial distribution of pesticides concentrations showed generally seaward decreasing trends, suggesting that anthropogenic activities at coastal areas have an important impact on pesticides pollution. Source identification indicated OCPs in some seawater samples might be from mixture of antifouling paint and dicofol usage, while history residues are main sources of OCPs in sediment. OAPs, especially for cyflufenamid and kresoxim-methyl, mainly come from agricultral and maricultural sewage input, and OPPs were speculated from currency transportation from surrounding areas. Ecological risk assessment showed that OPPs posed moderate to even high risks in most seawater sites. It appears that crustaceans are the most sensitive trophic species to OPPs among aquatic organisms, followed by fish. According to the results of health risks proposed by the major aquatic products in Beibu Gulf (fish and shrimp), the selected pesticides pose no health risk to humans. Nevertheless, OCPs made the highest contribution to the total HQ values. Comprehensively considering the evaluation results of both ecological and health risks, more attention should be given on OPPs and OCPs pollution in the Beibu Gulf.